On the methodology of economics and the formalist revolution - Hutchison, T. W. (Terence Wilmot) (Cheltenham, UK ; Northampton, MA, USA : E. Elgar Pub., 2000)
This book examines the methodological problems confronting economists in the face of two major developments in the second half of the twentieth century.The philosophy of Ecoomics and the formalist revolution.
Includes bibliographical references and index.
rpm 10/03/14
loans
Keywords: Economics -- Methodology; Economics -- History